Educating the next generation of open scholars: approaches, tools, and tactics - Hall, Robyn (My University, 2019)
Those who teach and work with students at the undergraduate and graduate level can play an important role in shaping the future of scholarly communications. Drawing students’ attention to the myriad of ways that research and scholarship can be shared openly online can provide valuable opportunities for students to disseminate their own work, engage with the work of others, and develop copyright literacy and improved academic writing and communication skills. Additionally, exposing students to the socioeconomic processes that shape access to knowledge can influence how these budding academics approach scholarly activity and where they choose to publish in their future careers.
Presented on August 5-6 at the Force11 Scholarly Communications Institute (FSCI) held at UCLA in Los Angeles, California.
Keywords: open access; copyright; open pedagogy